2x-4*5-3x-1*2=4

Simple and best practice solution for 2x-4*5-3x-1*2=4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2x-4*5-3x-1*2=4 equation:


Simplifying
2x + -4 * 5 + -3x + -1 * 2 = 4

Multiply -4 * 5
2x + -20 + -3x + -1 * 2 = 4

Multiply -1 * 2
2x + -20 + -3x + -2 = 4

Reorder the terms:
-20 + -2 + 2x + -3x = 4

Combine like terms: -20 + -2 = -22
-22 + 2x + -3x = 4

Combine like terms: 2x + -3x = -1x
-22 + -1x = 4

Solving
-22 + -1x = 4

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '22' to each side of the equation.
-22 + 22 + -1x = 4 + 22

Combine like terms: -22 + 22 = 0
0 + -1x = 4 + 22
-1x = 4 + 22

Combine like terms: 4 + 22 = 26
-1x = 26

Divide each side by '-1'.
x = -26

Simplifying
x = -26

See similar equations:

| 3*(n+.333)=2 | | (4.8x+8x)=(6.8-6.8) | | 3t+6=-4 | | (5z-6y)(5z+6y)= | | (4.8x+8x)(6.8-6.8)= | | 3[x+2]=9 | | (5z-6y)(5z+6)= | | 3x(n+.333)=2 | | (4.8x+8x)= | | x^2+88x=0 | | 5-3(2x-1)=4(x-5)+6 | | (19p^8q^2)x(-5p^7q^7)= | | 230=-75x+5 | | 14=5z | | 6+8=5z | | 3(4x+1)=2x-8x | | 3x-(3-4)=-17 | | 12cosx-6=0 | | 3(4x-1)=2x-8x | | 2x^4+7x^3-3x^2-5x-1=0 | | (-11)/(16x) | | 15-2c=7 | | 5/9(F-32)=-62.1 | | t=3n+3 | | 2(x+1)=3x+-3 | | 81-7+6= | | -6=n/3-10 | | 32x+24y+64= | | 9*x^6+15*x^4-x^2-6*x+1=0 | | 5/9(F-32)=25 | | 2n-14=81 | | 7(v+4)-3v=2(2v+2)-11 |

Equations solver categories